High prevalence of overweight/obesity and central obesity among women in a rural district of Nepal in 2012–2013: a population-based study - Chandra Yogal; Chandra Yogal; Astrid Kamilla Stunes; Astrid Kamilla Stunes; Sunila Shakya; Biraj Karmarcharya; Rajendra Koju; Mats P. Mosti; Mats P. Mosti; Miriam K. Gustafsson; Miriam K. Gustafsson; Bjørn Olav Åsvold; et al. (Frontiers in Public Health)
BackgroundThe prevalence of overweight is rapidly escalating, especially in South-Asia. We aimed to estimate the prevalence of overweight/obesity and central obesity, and associated risk factors among women in a rural setting of Nepal.MethodsA cross-sectional study addressing reproductive health and non-communicable diseases (NCDs) was conducted 2012–2013 in a rural district of Nepal. Married, non-pregnant women ≥15 years of age were included. Height, weight, and waist circumference (WC) were measured, and body mass index (BMI) calculated. WHO cut-offs for Asians were used to assess the prevalence of overweight (23.0–27.4 kg/m2), obesity (≥ 27.5 kg/m2) and central obesity (WC ≥ 80 cm). Data concerning socioeconomic and lifestyle factors were collected.ResultsAltogether, 1,391 women 43.1 ± 14.4 years of age were included. The majority belonged to the Adhivasi/Janajati ethnicity, were uneducated and worked in agriculture. Altogether, 30.5% were overweight, 12.0% obese, and 34.2% centrally obese; 25.7% were both overweight/obese and centrally obese. Underweight (< 18.5 kg/m2) was observed in 9.6%. Among women with normal weight or underweight, 14.9 and 15.3% had central obesity, respectively. Hypertension was observed in 13.4% and was associated with both overweight/obesity and central obesity. Instant noodle intake ≥2 times weekly was associated with increased prevalence of central obesity and overweight/obesity.ConclusionWe observed a high prevalence of overweight/obesity and central obesity among women in a rural district of Nepal, which entails an increased risk of metabolic complications and NCDs. Our findings underscore the need for public health programs addressing nutritional patterns and physical activity to prevent obesity.